2019
DOI: 10.18502/jdt.v15i6.330
|View full text |Cite
|
Sign up to set email alerts
|

Polymerization Shrinkage of Five Bulk-Fill Composite Resins in Comparison with a Conventional Composite Resin

Abstract: Objectives: The polymerization shrinkage of methacrylate-based composites is among the most important causes of failure of composite restorations. The manufacturers claim that bulk-fill composites have a lower polymerization shrinkage than conventional composites. This study aimed to assess the polymerization shrinkage of five bulk-fill composites in comparison with a conventional composite. Materials and Methods: In this in-vitro experimental study, composite discs (n=30) were fabricated using everX Pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
23
0
10

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(37 citation statements)
references
References 28 publications
4
23
0
10
Order By: Relevance
“…Filtek Z350 was used in the study as a conventional RBC to act as a control, ultimately exhibiting no significant difference in the VPS compared with the bulk-fill RBCs. This was in agreement with a study by Abbasi et al, 31 whereby no significant difference was observed between the conventional and bulk-fill RBC in terms of VPS. Another study by Rizzante et al 32 examined the VPS of bulk-fill composites using μ-CT concluding that the bulk-fill RBCs provided similar results to the conventional RBC.…”
Section: Discussionsupporting
confidence: 94%
“…Filtek Z350 was used in the study as a conventional RBC to act as a control, ultimately exhibiting no significant difference in the VPS compared with the bulk-fill RBCs. This was in agreement with a study by Abbasi et al, 31 whereby no significant difference was observed between the conventional and bulk-fill RBC in terms of VPS. Another study by Rizzante et al 32 examined the VPS of bulk-fill composites using μ-CT concluding that the bulk-fill RBCs provided similar results to the conventional RBC.…”
Section: Discussionsupporting
confidence: 94%
“…También, este tipo de resina tiene mayor resistencia al estrés ya que contiene dos monómeros de metacrilato que actúan para disminuir el estrés por polimerización y de esta manera reduce el riesgo de tener filtración marginal. (3,4) Otras de las ventajas de las resinas Bulk Fill es que ofrecen mejores condiciones de uso ya que poseen nuevos fotoiniciadores que contribuyen a la translucidez, permitiendo una mayor penetración de la luz LED. Además, poseen alta viscosidad debido a las ondas sónicas que presenta el material y esto aumenta la fluidez y mejora la adaptación marginal.…”
Section: Dedicatoriaunclassified
“…La estabilidad cromática es una propiedad óptica que se define como la resistencia al cambio de color. (4,5) Estas resinas, pueden generar cambio de coloración por diversos factores extrínsecos e intrínsecos. Los factores intrínsecos que pueden afectar la estabilidad del color se adquieren del medio bucal y se forma por la acumulación de placa.…”
Section: Dedicatoriaunclassified
See 2 more Smart Citations